Sporadic Burkitt Lymphoma First Presenting as Painful Gingival Swellings and Tooth Hypermobility: A Life-Saving Referral - Erofili Papadopoulou; Maria Kouri; Dimitrios Velonis; Anastasia Andreou; Maria Georgaki; Spyridon Damaskos; Evangelia Piperi; Konstantina Delli; Ioannis K. Karoussis; Antonia Vlachou; Georgia Avgerinou; Antonis Kattamis; et al. (Dentistry Journal)
Background: Burkitt lymphoma (BL) is an aggressive non-Hodgkin lymphoma (NHL), subdivided into endemic, sporadic, and immunodeficiency-associated forms. While jaw lesions are common in endemic BL, they are infrequent in sporadic cases, only rarely constituting the first manifestation of the disease. The aim of this study is to present a rare pediatric case of sporadic BL first manifesting as gingival swellings and tooth hypermobility and provide a review of all the published sporadic BL case reports as the first sign of disease. Case report: An 11-year-old Caucasian female was referred for the evaluation of hypermobility of posterior lower teeth, associated with painful gingival swellings of 20 days duration. Clinical examination revealed right facial asymmetry and bilateral prominent swellings of the posterior lower gingiva. A panoramic radiograph revealed ill-defined radiolucent lesions in the posterior mandible bilaterally. On computed tomography, soft-tissue masses were identified along the mandibular ramus extending into the maxillary sinus bilaterally. The histopathologic and immunohistochemical analyses of the lesions led to a diagnosis of Burkitt lymphoma (BL). The patient underwent a full staging work-up, revealing bone marrow involvement and widespread disease. A multi-chemotherapy regimen was initiated with the regression of oral lesions and symptoms within a few weeks and complete disease remission after nine chemotherapy cycles. The patient remains free of disease 11 years later. Conclusions: This case underscores the critical importance of the timely diagnosis and life-saving referral of rapidly growing jaw lesions, which may represent the first sign of an underlying lymphoreticular malignancy with aggressive course, such as BL.